PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN TAMU MENGINAP DI PLATARAN UBUD HOTEL & SPA - Riska Martiantari, Ni Wayan; Agung Ayu Arun Suwi Arianty, Anak; Ayu Melistyari Dewi, I Gusti; Ayu Eka Suwintari, I Gusti (Berajah Journal, 2024)
Promotion is an important factor in guests' decision to stay. Besides that, price is an aspect that is clearly visible to consumers and is also a factor in influencing consumers' decision to stay. Plataran Ubud Hotel & Spa has carried out several promotions to increase guests' interest in staying, but the number of rooms sold is still decreasing. The decrease in the number of rooms sold was also due to indications of high room prices for consumers. Plataran Ubud Hotel & Spa receives comments and reviews written by guests on the TripAdvisor, Booking.com and Google Review sites regarding high prices. This research aims to determine the influence of promotions and prices on guests' decisions to stay at Plataran Ubud Hotel & Spa. The research method used is quantitative correlational with data collection techniques, namely observation, questionnaires, interviews, and documentation. This research used 40 respondents using the Quota Sampling sampling technique and the sample size was based on the Hair et al. The results of the research show that there is a partial positive and significant influence between promotion on guests' decision to stay, there is a partial positive and significant influence between price on the decision to stay, and there is a simultaneous positive and significant influence between promotion and price on the decision to stay at Plataran Ubud Hotel & Spa.